High-Salt Diet in the Pre- and Postweaning Periods Leads to Amygdala Oxidative Stress and Changes in Locomotion and Anxiety-Like Behaviors of Male Wistar Rats - Leal, Pedro Ernesto de Pinho Tavares; da Silva, Alexandre Alves; Rocha-Gomes, Arthur; Riul, Tania Regina; Cunha, Rennan Augusto; Reichetzeder, Christoph; Villela, Daniel Campos (Frontiers in Behavioral Neuroscience, 2022)
This study aimed to evaluate the amygdala redox status and anxiety-like behaviors in adulthood, after inclusion of high-salt diet in two periods: pre-conception, gestation and lactation (pre-weaning); and only after weaning (post-weaning). Initially, 18 females and 9 male Wistar rats received a standard (n = 9 females and 4 males) or a high-salt diet (n = 9 females and 5 males) for 120 days. After mating, females continued to receive the aforementioned diets during gestation and lactation. Weaning occurred at 21 days-old and the male offspring were subdivided: C-C - offspring of standard diet fed dams who received a standard diet after weaning (n = 9-11); C-HS - offspring of standard diet fed dams who received a high-salt diet after weaning (n = 9-11); HS-C - offspring of high-salt diet fed dams who received a standard diet after weaning (n = 9-11); HS-HS - offspring of high-salt diet fed dams who received a high-salt diet after weaning (n = 9-11). At adulthood, the male offspring performed the Elevated Plus Maze and Open Field tests. At 152 days-old the offspring were euthanized and the amygdala was removed for redox state analysis. The HS-HS group showed higher locomotion and rearing frequency in the Open Field test. These results indicate that this group developed hyperactivity. The C-HS group had a higher ratio of entries and time spent in the open arms of the Elevated Plus Maze test, in addition to a higher head-dipping frequency. These results suggest less anxiety-like behaviors. In the analysis of the redox state, less activity of antioxidant enzymes and higher levels of TBARS in the amygdala were shown in the amygdala of animals that received a high-salt diet regardless of the period (pre- or post-weaning). In conclusion, the high-salt diet promoted hyperactivity when administered in the pre- and post-weaning periods. In animals that received only in the post-weaning period, the addition of salt induced a reduction in anxiety-like behaviors. Also, regardless of the period, salt provided amygdala oxidative stress, which may be linked to the observed behaviors.